Baseline comorbidities in a skin cancer prevention trial in Bangladesh. (17th April 2013) - Argos, Maria; Rahman, Mahfuzar; Parvez, Faruque; Dignam, James; Islam, Tariqul; Quasem, Iftekhar; K. Hore, Samar; T. Haider, Ahmed; Hossain, Zahid; I. Patwary, Tazul; Rakibuz‐Zaman, Muhammad; Sarwar, Golam; et al.
Abstract Background Epidemiologic research suggests that increased cancer risk due to chronic arsenic exposure persists for several decades even after the exposure has terminated. Observational studies suggest that antioxidants exert a protective effect on arsenical skin lesions and cancers among those chronically exposed to arsenic through drinking water. This study reports on the design, methods and baseline analyses from the Bangladesh Vitamin E and Selenium Trial (BEST), a population‐based chemoprevention study conducted among adults in Bangladesh with visible arsenic toxicity. Materials and methods Bangladesh Vitamin E and Selenium Trial is a 2×2 full factorial, double‐blind, randomized controlled trial of 7000 adults having manifest arsenical skin lesions evaluating the efficacy of 6‐year supplementation with alpha‐tocopherol (100 mg daily) and L‐selenomethionine (200 μg daily) for the prevention of nonmelanoma skin cancer. Results In cross‐sectional analyses, we observed significant associations of skin lesion severity with male gender (female prevalence odds ratio (POR) = 0·87; 95% CI = 0·79–0·96), older age (aged 36–45 years, POR = 1·27; 95% CI = 1·13–1·42; aged 46–55 years, POR = 1·44; 95% CI = 1·27–1·64 and aged 56–65 years, POR = 1·50; 95% CI = 1·26–1·78 compared with aged 25–35 years), hypertension (POR = 1·29; 95% CI = 1·08–1·55), diabetes (POR = 2·13; 95% CI = 1·32–3·46), asthma (POR = 1·55; 95% CI = 1·03–2·32) and peptic ulcer disease (POR = 1·20; 95% CI = 1·07–1·35). Conclusions We report novel associations between arsenical skin lesions with several common chronic diseases. With the rapidly increasing burden of preventable cancers in developing countries, efficient and feasible chemoprevention study designs and approaches, such as employed in BEST, may prove both timely and potentially beneficial in conceiving cancer chemoprevention trials in Bangladesh and beyond.